The Electrochemistry of Vitamin B12 in Ionic Liquids and Its Use in the Electrocatalytic Reduction of Vicinal Dibromoalkanes - Lagunas, M.; Silvester, Debbie; Aldous, L.; Compton, R. (Wiley - VCH Verlag GmbH & Co. KGaA, 2006)
We present the first electrochemical study in ionic liquid media of cyanocobalamin (vitamin B12), a biologically important molecule, and show its suitability as catalyst in the electroreduction of dibromoalkanes.